How to Jump Start Vietnam's Economy? - Inoue, Keiko (World Bank, Washington, DC, 2020)
COVID-19 has caused an unprecedented shock to the global economy. While Vietnam has shown resilience, the pandemic has resulted in a supply shock as regular work and supply chains are disrupted. It has also caused a demand shock as people cut back their consumption of several services and commodities, not only for restaurants and travel, but throughout the economy given their extreme uncertainties about their economic future. So far, the Government has been very effective in containing the pandemic with a limited number of cases and no registered deaths. The Government has also been active in providing immediate support to the most affected people and businesses through the easing of monetary and credit policies as well as the implementation of a series of fiscal measures. Hopefully the economy will withhold and start to rebound gradually. But it won’t be easy to restart a modern interconnected global economy while the world awaits the arrival of a vaccine that has yet to be discovered. Recovery will begin when health officials can assure people that the new coronavirus has been contained and the mainstream availability of test kits, both to identify the infected and people with antibodies.